ANALISIS MARKETING MIX SYARIAH PADA PRODUK GRIYA HASANAH DALAM PENINGKATAN JUMLAH NASABAH PADA BANK SYARIAH INDONESIA KCP DIPONEGORO SUMENEP - Rahman, Holilur; Annisa, Annisa; Zahrah, Alfian Rihtuz; Lisniati, Lisniati (Reflektika, 2020)
It is hoped that the mager policy of three Islamic banks in Indonesia will provide a choice of new financial institutions for Islamic-based communities while at the same time increasing the national economy. The purpose of this study is to determine the implementation of sharia marketing mix at Bank Syariah Indonesia KCP Diponegoro. This research uses a qualitative descriptive method by applying a case study approach that aims to obtain information directly from informants. Data collection techniques using observation, interviews and documentation. Based on the results of this study, it shows that the application of marketing strategies using a marketing mix (marketing mix), the products offered are very varied according to the needs of society for the present and future, while from very cheap and flexible prices to make transactions. For an easily accessible location, then promotions using personal selling, brochures and others. However, the impact of implementing sharia marketing mix on griya hasanah products is not good, because recently the product that has been favored is Pre-Retirement Blessings